Using ISO 9000 to improve business processes (AT&T Corporate Quality Office [S.l.]US, 1995)
Highlights 8 important lessons learned by AT&T organizations who improved their business processes, as a result of compliance with ISO 9000. Provides information, and addresses some of the concerns that business managers have about ISO 9000. These concerns include questions about the requirements of ISO 9000; the cost involved in the ISO 9000 compliance effort; documents required; and benefits to participating organizations.
Bibliography: p. 233-242. Located in the Learning Resource Centre.